Not Asian Anymore: Reconstruction of the History, Evolution, and Dispersal of the “Asian” Lineage of CPV-2c - Giovanni Franzo; Francesco Mira; Giorgia Schirò; Marta Canuti (Viruses, 2023)
Variability has been one of the hallmarks of canine parvovirus type 2 (CPV-2) since its discovery, and several lineages and antigenic variants have emerged. Among these, a group of viruses commonly called Asian CPV-2c has recently been reported with increasing frequency in different regions. Currently, its global epidemiology and evolution are essentially unknown. The present work deals with this information gap by evaluating, via sequence, phylodynamic, and phylogeographic analyses, all the complete coding sequences of strains classified as Asian CPV-2c based on a combination of amino acid markers and phylogenetic analysis. After its estimated origin around 2008, this lineage circulated undetected in Asia until approximately 2012, when an expansion in viral population size and geographical distribution occurred, involving Africa, Europe, and North America. Asia was predicted to be the main nucleus of viral dispersal, leading to multiple introduction events in other continents/countries, where infection establishment, persistence, and rapid evolution occurred. Although the dog is the main host, other non-canine species were also involved, demonstrating the host plasticity of this lineage. Finally, although most of the strains showed an amino acid motif considered characteristic of this lineage, several exceptions were observed, potentially due to convergent evolution or reversion phenomena.